Choosing PD-1 Inhibitors in Oncology Setting, Left or Right?—Lessons From Value Assessment With ASCO-VF and ESMO-MCBS - Jiang, Qian; Feng, Mei; Li, Youping; Lang, Jinyi; Wei, Hua; Yu, Ting (Frontiers in Pharmacology, 2020)
Background: Influx of innovative therapies and dramatic rise in prices have been prompting value-driven decision-making. Both the American Society of Clinical Oncology (ASCO) and the European Society for Medical Oncology (ESMO) have independently proposed value assessment frameworks. Objectives: To comprehensively examine the value of nivolumab and pembrolizumab by two value assessment frameworks with a cohort of published randomized controlled trials and offer insight into the association between these two frameworks. Methods: Trials were identified with a cutoff date of Nov 30th, 2019. Receiver operating characteristic curves were generated to establish the predictive value of ASCO-VF score to meet ESMO-MCBS grade and discriminate the agreement of these two value assessment tools. Spearman correlation was used to assess the association between monthly cost and ASCO-VF score/ESMO-MCBS grade. Results: 19 randomized controlled trials were eligible. seven (36.8%) trials were of treatment included nivolumab while 12 (63.2%) pembrolizumab. 8 (42.1%) of the trials were of treatments for non-small-cell lung cancer, 5 (26.3%) for melanoma, 2 (10.5%) were for head and neck squamous cell carcinoma, 2 (10.5%) for gastric or gastro-oesophageal junction cancer and 1 (5.3%) for urothelial cancer and renal-cell carcinoma respectively. ASCO scores ranged from 7 to 94.7 with median 40.90. 11 (57.9%) trials met the ESMO criteria for meaningful value achieved. Of 14 trials not meeting the ASCO cutoff score, only 8 did not meet the meaningful ESMO criteria. Agreement between these two frameworks thresholds was only fair (κ = 0.412, P＜0.05). A negative correlation was noted between increment monthly cost and value assessment results. Conclusion: There is only fair correlation between ASCO and ESMO value assessment frameworks. Not all treatment with nivolumab and pembrolizumab meet valuable thresholds.